A Study on the Appropriateness of Vocabulary in The Grade IX English Textbook: Perspectives of Teachers and Students - Lulu Angguni; Suharmoko Suharmoko; Miftahulfadlik Dabamona (Universitas Nurul Jadid, 2026)
Vocabulary appropriateness in EFL textbooks remains underexamined in Southwest Papua, where regional disparities in English exposure and limited supplementary resources create conditions distinct from those commonly discussed in the literature. This study examined teacher and student perspectives on vocabulary in the Grade IX English textbook published by Intan Pariwara (Bahasa Inggris untuk SMP/MTs Kelas 9) at MTs Negeri Kota Sorong, Southwest Papua, a context where English is largely confined to the classroom. Six participants were recruited through purposive sampling: two English teachers and four Grade IX students, whose combination enabled triangulation between instructional context and lived experience. Data were collected via semi-structured interviews conducted in Bahasa Indonesia and translated into English for reporting purposes, then analyzed using the thematic analysis framework of Naeem et al. (2023), with theoretical grounding in Nation (2024), McGrath (2016), and Beck et al. (2013). Four themes emerged: perceived difficulty, vocabulary type, adequacy of support, and learning and teaching strategies. Teachers rated the vocabulary as moderately difficult, while students consistently described it as genuinely difficult, particularly the academic and scientific vocabulary in report texts, which concentrates in Tier 2 and Tier 3 categories. Both groups considered in-text vocabulary support insufficient: glossaries were absent from most units, per-unit word lists were limited, and scaffolding was minimal. Consequently, students relied on tools such as Google Translate and ChatGPT not out of preference but due to limited alternatives, a pattern teachers also acknowledged. Overall, the textbook was considered only partially appropriate, and recommended priority revisions include per-unit vocabulary lists, explicit scaffolding for report text vocabulary, and a comprehensive end-of-book glossary.